농가의 고령화가 소득불평등에 미치는 영향 : 연령효과의 실증분석을 중심으로 - 윤영석 (한국농촌경제연구원, 2013)
This study is aimed to estimate the age effect on income inequality of farm households which is resulted from the aging of farm operators and to draw out its counter-strategy through the results of this analysis. The panel generalized least squares (PGLS) method is used to examine the age effects. The data used are panel data which are from 1993 to 2011 of the farm household economy survey. The results of study demonstrate that a positive relationship exists between the age of farm operator and its relative contribution ratio to income inequality of farm households. This means that the more the age of farm operator, the more the contribution ratio to income inequality of farm households. And it also represents that relative contribution ratio of youthful farm operator to income inequality of farm households is higher than another age group.
Keywords: 연령효과; 패널GSL; 소득불평등; 대수편차평균; Age Effects; panal generalized least squares; income inequality; mean logarithmic deviation